Who Owes? Class Struggle, Inequality and the Political Economy of Leverage as Power in the 21st Century - Stefano Sgambati (City, University of London, City Political Economy Research Centre (CITYPERC), 2021)
The prevalent consensus in critical social sciences is that finance articulates the world economy as a global hierarchy of creditor-debtor relations that reproduce and further aggravate existing income and wealth inequalities. Class struggle is conformingly understood as a conflict between elite creditors, members of the global top 1 percent of wealth holders, and mass debtors burdened by growing costs of servicing public and private debts. The article offers an alternative understanding of how debt, inequality and class relate to one another. At its basis is the recognition that over the past four decades finance has empowered upper class borrowers, including the top 1 percent, as it has magnified their capacity to generate capital gains and capture greater wealth and income shares via levered-up investments and other forms of 'positioning' in financial and property markets. The article thus provides a political economy of leverage as power and shows how contemporary global finance has not given shape to a distributional conflict between creditors and debtors as two distinct classes, but has set debtors against debtors, and namely the greater borrowers versus the lesser ones.
Keywords: 330; Class; debt; inequality; leverage; power; finance